A Way of Qualifying Amine Based Capture Technologies with Respect to Health and Environmental Properties. (January 2016) - Helgesen, Laila Iren; Gjernes, Erik
Abstract: The Norwegian full scale CO2 capture project Mongstad (CCM) gained extensive knowledge and experience during seven years of preparation and planning including activities to qualify technology. Initially amine based capture technologies were the only viable choice of technology and it was very early stated the need for more knowledge to assist assessing the health and environmental (H&E) risk of these technologies. Emissions to air of possibly carcinogenic substances were flagged as a potential showstopper in an early phase of the project. A comprehensive research program was initiated to identify and close knowledge gaps with respect to formation potential and toxicity level of these compounds known as nitrosamines and nitramines. This has been scientifically founded work done by universities, research institutes and scientific bodies. The results consist of well documented procedures for sampling and chemical analysis, atmospheric chemistry reaction schemes and kinetics, several dispersion and deposition models and simulation results of environmental fate and impact on human health. The latter has been established through own toxicity testing and extensive literature search for toxicity data. Knowledge gained during technology qualification for CCM was to a large extent site specific for Mongstad and technology specific covered by non-disclosure agreements. However, a lot of the basic H&E information needed to carry out risk assessment is of general character and possible to transfer to capture technology suppliers and capture plants under planning and installation elsewhere. This has been done by Gassnova through making publicly available an impressive set of reports, 63 all together, on its web page. This paper will present how this comprehensive research program was executed and how the CCM project used the developed methods, models and procedures in the process of qualifying capture technology for the CCM plant. All in all this practice has proven to be both well fitted and useful in differentiating between the five capture technologies from Aker Clean Carbon, Mitsubishi Heavy Industries, Siemens, Huaneng Ceri Powerspan Joint Venture and Alstom Carbon Capture competing for the CCM contract. The CCM project was terminated before final choice of technology was conducted.